Online recovery support meetings can help mitigate the public health consequences of COVID-19 for individuals with substance use disorder. (February 2021) - Bergman, Brandon G.; Kelly, John F.; Fava, Maurizio; Eden Evins, A.
Abstract: For people with current and remitted substance use disorder (SUD), the COVID-19 pandemic increases risk for symptom exacerbation and relapse through added stressors and reduced service access. In response, mutual-help groups and recovery community organizations have increased access to online recovery support meetings. However, rigorous studies examining online recovery support meeting participation to inform best practices have not yet been conducted. In the absence of such studies, a review of relevant literature, considered in context of potential barriers and drawbacks, suggests the risk-to-benefit ratio is favorable. Particularly given limited in-person SUD service access resulting from COVID-19 precautions, online recovery support meetings may help mitigate a key public health problem during an ongoing, public health pandemic.